2014
DOI: 10.4236/ijcm.2014.55036
|View full text |Cite
|
Sign up to set email alerts
|

Adherence in CABG Patients: An Empirical Test of a Health Behavior Model

Abstract: To benefit from a Coronary Artery Bypass Graft Surgery (CABG), patients must adhere to their therapeutic regimen. To test the extent of which the Information-Motivation-Behavioral Skills (IMB) model constructs explain the variability in adherence behaviors in CABG patients, and also to examine the relationship between the IMB model constructs, CABG patients (N = 152) were randomly assigned to either an intervention group, or a standard care control group. They completed pretest measures, and were reassessed la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The participants with heart failure (HF),[ 26 27 28 29 30 31 32 33 ] coronary heart disease (CHD),[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] hypertension (HTN),[ 13 39 40 41 42 43 44 ] coronary artery bypass graft (CABG),[ 20 45 46 47 48 ] myocardial infarctions (MI),[ 17 19 49 50 51 ] patients with pacemaker,[ 52 ] heart valve disease,[ 53 ] and cardiac rehabilitation[ 18 ] were highest and lowest target groups in studied papers, respectively. The detailed characteristics of included studies are revealed in [ Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants with heart failure (HF),[ 26 27 28 29 30 31 32 33 ] coronary heart disease (CHD),[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] hypertension (HTN),[ 13 39 40 41 42 43 44 ] coronary artery bypass graft (CABG),[ 20 45 46 47 48 ] myocardial infarctions (MI),[ 17 19 49 50 51 ] patients with pacemaker,[ 52 ] heart valve disease,[ 53 ] and cardiac rehabilitation[ 18 ] were highest and lowest target groups in studied papers, respectively. The detailed characteristics of included studies are revealed in [ Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge and awareness about systolic and diastolic blood pressure using BAZNEF model,[ 42 ] increasing average time of physical activity among hypertensive patients based on TTM,[ 41 ] intervention HBM-based on nutritional behavior among patients with MI,[ 50 ] HBM-based educational program on nutritional knowledge and behaviors among CABG patients,[ 45 46 ] improving motivation for health behaviors,[ 48 ] and active education and prevention of recurrent MI[ 51 ] revealed significant difference on educational outcomes after interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation